Retroperitoneal Lymph Nodes in Transitional Cell Carcinoma of the Kidney and Ureter - Shilajit D. Kundu; Scott E. Eggener (Advances in Urology)
The incidence of transitional cell carcinoma of the kidney and ureter is low and for that reason limited data exists regarding the appropriate management of regional retroperitoneal lymph nodes. Lymph node metastases have consistently been associated with an adverse prognosis. However, five-year cancer-specific survival following nephroureterectomy and lymphadenectomy for patients with lymph node involvement ranges from 0–39%, suggesting a therapeutic benefit. This review covers the primary tumor characteristics associated with lymph node involvement, imaging of the lymph nodes, as well as the rationale, role, patient selection, suggested anatomic templates, and technical considerations for lymphadenectomy.